Forensic Evaluation of Child Sexual Abuse Cases Applying to the Child Advocacy Center in Aydın Province Between 2018-2022: A Retrospective Descriptive Study - Erdoğan, Merthan; Erel, Özlem (The Bulletin of Legal Medicine, 2024)
Objective: In this study, it is aimed to evaluate the children who have been victims of sexual abuse and have applied to Child Advocacy Center.Methods: This study, designed as a retrospective and descriptive study, included cases referred with allegations of sexual abuse.Results: It was determined that most of the victims came from nuclear families (51%) and that the most common location of the incident was district centers (51.8%). Almost all of the alleged perpetrators were male (98.4%) and acted alone (89.9%), with an average age of 27.1 years. It was observed that girls were most frequently abused by boyfriends (13%), while boys were most commonly abused by peers and friends (35.2%). The incidents of abuse were most commonly shared with parents (43.6%), and it was found that intrafamilial abuse (50.7%) tended to recur more often than extrafamilial abuse (34.1%), with number of reported cases increasing over years. It was noted that 43.2% of the victims described interfemoral contact or rubbing, 37% of the cases were examined, and in 4.2%, no examination was necessary due to pregnancy. Vaginal examination revealed that the most common finding was a tear older than 10 days (60%), while anal examination showed no findings in the majority of cases (75.2%).Conclusion: It was observed that the majority of the suspects were familiar individuals. It was particularly noted that intrafamilial abuse incidents tended to recur multiple times and that the time between the incident and the report was longer compared to cases involving other suspects.
Keywords: Child abuse, Child abuse-sexual, Sexual abuse